SAS 9.4 Output Delivery System, 4th Edition - Institute, SAS (SAS Institute, 2015)
Provides usage information and examples for Output Delivery System (ODS) capabilities. The document describes a wide range of formatting options and shows how to gain greater flexibility in generating, storing, and reproducing SAS procedure and DATA step output.